The Synchronization Process of Legal System in Tunggu Tubang Land Certification - Firman Muntaqo; Mashudi Mashudi; Murzal Zaidan; Fahmi Yoesmar Ar-Rasyidi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
The study on the Tunggu Tubang Land Certification in the Semende area aims to examine 3 (three) problems, they are aspects of historical and sociological rechts supporting and inhibiting; synchronization of the legal system, as well as; alternative arrangements for facilitation of Tunggu Tubang land certification. The research used a normative juridical approach. The results of the study state that the study of synchronization of the legal system, there are no obstacles to the certification of Tunggu Tubang land, with the argument that the Tunggu Tubang land comes from private land (land of customary land), or civil rights/private rights/privaatrecht according to the western legal system, and does not include the power of rights. The Ulayat as common property of the community, therefore basically can be certified. Alternative facilitation of Tunggu Tubang land certification can be done by heeding the legal concept of the Tunggu Tubang Institution which stipulates that, Tunggu Tubang which contains the principles: There is land that is jointly owned by the descendants of the female line of the founder of Tunggu Tubang; there is an administrator who is not entitled to sell/transfer the land of Tunggu Tubang, but only manages it for the benefit of the descendants of the founder of Tunggu Tubang.